Influencia de la temperatura de recocido sobre las propiedades ópticas, estructurales y morfológicas de la película delgada de ZNO dopada con CU obtenida por rociado pirolítico - Castro Campos, Eberth Isaac (2018)
In this thesis work I´ve studied the influence of annealing temperature over to rugosity, transmitance and cristallite size of ZnO:Cu 3 % thin films. The ZnO:Cu 3% thin films was synthetisized over glass substrates by spray pyrolisys technique using zinc acetate dyhidrate[(32)2.22] and copper chloride dyhidrate[2.22] as precursor solutions mixed in ethanol. The diffraction patterns of ZnO:Cu 3% thin films both without annealing and annealed at 400, 450 and 500 ℃ indicates that all samples are polycrystalline with wurtzita hexagonal structure. The preferred plane of growth was (002), decreasing the intensity of its peak only in the sample annealed at 400 ℃. The crystallite size for the sample without annealing was 25.82 nm and for the samples annealed at 400, 450 and 500 ℃ of 18.78, 26.33 and 29.23 nm respectively. The images obtained by atomic force microscopy indicate that the average roughness (Ra) increases with annealing temperature except for the sample annealed at 400 ℃ which decreases. Analyzes in the UV-Vis indicate that these films have high transmittance greater than 80% and that the absorbance is minimal. The band gap for sample without annealing was 3.256 eV and for the samples annealed at 400, 450 and 500 ℃ of 3.256, 3.263 and 3.257 eV respectively